Strengthening Small Business Labor Potential for Economic Growth in Uzbekistan: Memperkuat Potensi Tenaga Kerja Usaha Kecil untuk Pertumbuhan Ekonomi di Uzbekistan - Egamberdieva Barnakhon Gulamjanovna (Academia Open, 2025)
General Background: Small businesses play a crucial role in driving economic growth, particularly in developing countries. Specific Background: In Uzbekistan, the government has prioritized small business development through various policies aimed at enhancing labor potential. Knowledge Gap: However, there is limited understanding of how labor potential within small businesses directly influences economic performance in this context. Aims: This study aims to explore the relationship between labor potential in small businesses and economic growth, focusing on Uzbekistan, using a mixed-methods approach. Results: The study finds that strategic investments in workforce development, entrepreneurial capacity, and institutional support significantly improve labor productivity, business outcomes, and contribute to national economic growth. Data from 200 businesses, 40 interviews, and case studies show the effectiveness of Uzbekistan's policies, including tax incentives and training programs. Novelty: This research provides a comprehensive analysis of how labor management and government policies impact small business success in Uzbekistan, filling a critical gap in existing literature. Implications: The findings suggest that enhanced labor skills and institutional support are key drivers of small business growth and sustainable economic development, with policy recommendations for strengthening labor potential in similar economies. Highlights: Labor potential drives small business growth and economic development. Uzbekistan’s policies support productivity through tax incentives and training programs. Workforce development is key to long-term economic sustainability. Keywords: Small businesses, labor potential, economic growth, Uzbekistan, policy support